PENYULUHAN DAN PELATIHAN PERILAKU HIDUP BERSIH DAN SEHAT PADA MASYARAKAT DALAM RANGKA MENEKAN SEBARAN COVID-19 DI KELURAHAN CISALAK KOTA DEPOK - Diana Irvindiaty Hendrawan; Melati Ferianita Fachrul; Rositayanti Hadisoebroto; Widyo Astono; Bambang Iswanto; Tazkiaturrizki Tazkiaturrizki (Universitas Trisakti, 2022)
The Covid-19 pandemic has greatly affected human life. Clean and Healthy Lifestyle (PHBS) is a government program that needs to be implemented in the community. The implementation of PHBS can prevent the spread of the Corona Virus. This Community Service (PkM) activity aims to provide counseling regarding the implementation of PHBS as an effort to avoid the Corona Virus and to provide assistance for portable hand washing equipment to be used by the public in public places. The method used is counseling and training which is carried out partly online and partly offline with 75 participants from the community. The location of the counseling and training is divided into 2 (two) places, namely the Al-Amin Mosque, RW 12, Cisalak Village and the Cisalak Village Office Hall, Depok. The results of this PkM are getting public understanding about PHBS as an effort to prevent the spread of the Covid 19 Virus and the availability of a portable sink for washing hands as one of the requirements for implementing PHBS. 2 (two) units of handwashing wastel were handed over to the Mushola and the Cisalak Sub-District Office, which was a contribution from the PKM Team to the community.